1995
DOI: 10.1037/0021-843x.104.3.517
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of latent depressive schemas in formerly depressed individuals.

Abstract: Detecting the effects of latent depressive schemas constitutes an important step toward validating A. T. Beck's (1967) tenet of the depressive cognitive style as a causal factor in the onset and relapse of major depression. The authors examined whether a sample of formerly clinically depressed individuals continued to exhibit a negatively biased information-processing style in the absence of concurrent depressed mood. As predicted, the scores of formerly depressed individuals on 2 questionnaires tapping dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
92
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 51 publications
8
92
0
3
Order By: Relevance
“…Moreover, these distorted cognitive processes can be found in at-risk (Dearing & Gotlib, 2009;Joormann, Talbot, & Gotlib, 2007;Kujawa et al, 2011;Taylor & Ingram, 1999) and remitted (Fritzsche et al, 2010;Gilboa & Gotlib, 1997;Hedlund & Rude, 1995;, 2010 depressed samples.…”
Section: Cognitive Biases and Vulnerability For Depressionmentioning
confidence: 99%
“…Moreover, these distorted cognitive processes can be found in at-risk (Dearing & Gotlib, 2009;Joormann, Talbot, & Gotlib, 2007;Kujawa et al, 2011;Taylor & Ingram, 1999) and remitted (Fritzsche et al, 2010;Gilboa & Gotlib, 1997;Hedlund & Rude, 1995;, 2010 depressed samples.…”
Section: Cognitive Biases and Vulnerability For Depressionmentioning
confidence: 99%
“…Prior studies with this task revealed differences in interpretative tendencies between depressed and non-depressed samples (e.g., Hedlund & Rude, 1995;Rude, Wenzlaff, Gibbs, Vane, & Whitney, 2002). In this study, each trial started with a fixation point at the left side of the screen (to elicit left-toright reading) followed by a stimulus display depicting either a neutral or an emotional scrambled sentence.…”
Section: Interpretation Bias a Computerized Version Of The Scrambledmentioning
confidence: 99%
“…La evidencia de un autoesquema marcadamente positivo en los sujetos no deprimidos se constata en numerosos estudios (Abramson y Alloy, 1981;Greenberg et al, 1988). Asimismo, la evidencia de sesgos positivos en el procesamiento de información para los sujetos no deprimidos, también se ha mostrado consistente en muchas investigaciones (Derry y Kuiper, 1981;Greenberg et al, 1988;Hedlund y Rude, 1995;Calev, 1996). Calev (1996) se refiere a este efecto como la «tendencia pollyana».…”
Section: Discussionunclassified
“…El meta-análisis realizado por Matt, Vázquez y Campbell (1992), avaló estos resultados para los estudios con poblaciones clínicas. Sin embargo, estudios posteriores no han logrado reproducir ese mismo efecto, utilizando diseños experimentales similares, e igualmente muesfras clínicas (Hedlund y Rude, 1995, Calev, 1996, Giménez, 2000. A la vista de estos resultados, la evidencia de un sesgo de memoria en el procesamiento de información autorreferente en personas deprimidas, considerando especialmente el recuerdo incidental, no se ha mostrado consistente.…”
unclassified